2020
DOI: 10.3390/polym12092090
|View full text |Cite
|
Sign up to set email alerts
|

Copernicia Prunifera Leaf Fiber: A Promising New Reinforcement for Epoxy Composites

Abstract: A basic characterization of novel epoxy matrix composites incorporated with up to 40 vol% of processed leaf fibers from the Copernicia prunifera palm tree, known as carnauba fibers, was performed. The tensile properties for the composite reinforced with 40 vol% of carnauba fibers showed an increase (40%) in the tensile strength and (69%) for the elastic modulus. All composites presented superior elongation values in comparison to neat epoxy. Izod impact tests complemented by fibers/matrix interfacial strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 48 publications
4
11
0
Order By: Relevance
“…Finally, a third stage, with a mass loss of 12.04% up to 700 °C, is attributed to inorganic residues of the final degradation of the resin. Similar events for epoxy resin were reported by Junio et al [ 52 ] and Silva et al [ 54 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Finally, a third stage, with a mass loss of 12.04% up to 700 °C, is attributed to inorganic residues of the final degradation of the resin. Similar events for epoxy resin were reported by Junio et al [ 52 ] and Silva et al [ 54 ].…”
Section: Resultssupporting
confidence: 88%
“…The DSC curve for untreated and treated TVF, shown in Figure 7 b, initially presents endothermic peaks between 70–80 °C that refer to moisture loss and TVF T g . The T g found for TVF in this work was very similar to natural fibers previously studied, such as carnauba (107 °C) [ 52 ], caranan (64 °C) [ 66 ], PALF (75 °C) [ 72 ] and jute (61 °C) [ 73 ]. Although these events are slightly different from those approached by TG, they fall within the same temperature range.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“… Variation of Izod absorbed impact energy with the volume fraction of guaruman fiber in the epoxy matrix composites. Neat epoxy value obtained from [ 26 ]. …”
Section: Figurementioning
confidence: 99%
“…It was found that the reduction in tensile properties and improvement in modulus, when compared to the neat resin composites and date palm fiber composites, show advanced thermal and morphological properties. Junio et al [28] worked on Copernicia prunifera leaf fiber epoxy composites. The results showed a 40% increase in tensile properties and a 69% increase of the elastic modulus, when compared to the neat epoxy resin composites.…”
Section: Introductionmentioning
confidence: 99%